Critical notes about Noether's theorem (Part I) - CARFI’, David (Journal of Mathematical Economics and Finance; Vol 4 No 2 (2018): JMEF, Volume IV, Issue 2(7), Winter 2018, 2018)
In this brief critical notes, we state and prove the classic Noether's theorem, in a language and in the mood of modern Differential Geometry. This modern approach, on one hand, wants to stimulate a dialogue between the classic Noether's theorem version users and the modern differential geometry developers, on the other hand, it opens the way for some extensions of the theorem, with possible physical insights about the matter.